Asas Tanggung Jawab Negara Sebagai Dasar Pelaksanaan Perlindungan dan Pengelolaan Lingkungan Hidup - Sudi Fahmi (Fakultas Hukum Universitas Islam Indonesia, 2011)
Based on the principle of state responsibility, the state will guarantee that the utilization of natural resources will provide benefits for the greater well-being and quality of life, both present and future generations as a goal of the implementation of sustainable development. The problems that would be investigated are; first, how is the state responsibility as a basis of the implementation of environmental protection and management? Second, how is the implementation of state responsibility as a basis of the implementation of environmental protection and management? The method used in this research is juridical normative with regulation approach. The analyze method used is qualitative analysis. The research concludes that the principle of state responsibility position as the basis for the implementation of environmental protection and management means: 1) State guarantees that the utilization of natural resources would provide benefits for the greater well-being and quality of life, both present and future generations. 2) State guarantees the rights of citizen for a good and healthy living environment. 3) State prevents the use of natural resources activities that cause pollution and/ or damage the environment.Key words : State responsibility, environmental protection and management